Associations of Fish and Omega-3 Fatty Acids Consumption With the Risk of Venous Thromboembolism. A Meta-Analysis of Prospective Cohort Studies - Zhang, Yi; Ding, Jun; Guo, Hongbin; Liang, Jieyu; Li, Yusheng (Frontiers in Nutrition, 2020)
Objective: This study aims to investigate the effect of fish and omega-3 fatty acids consumption on the risk of VTE. Methods: A comprehensive literature search in the databases of PubMed, Web of Science and Embase (up to September 2020), was conducted to identify the prospective cohort studies concerning the associations of fish and omega-3 fatty acids consumption with the risk of VTE. The pooled relative risk (RR) of VTE for the highest versus lowest category of fish and omega-3 fatty acids consumption, as well as their corresponding 95% confidence interval (CI) were calculated. Results: A total of 7 articles with 8 prospective cohort studies were included. Specifically, 6 studies were related to fish consumption, and the overall multi-variable adjusted RR showed no significant relationship between fish consumption and the risk of VTE (RR=1.02, 95% CI: 0.93 to 1.11; P=0.709). In the 4 studies related to omega-3 fatty acids consumption, the overall multi-variable adjusted RR suggested that omega-3 fatty acids consumption was associated with a lower risk of VTE (RR=0.89, 95% CI: 0.80 to 0.98; P=0.024). Moreover, 2 studies were related to recurrent VTE, and the overall multi-variable adjusted RR demonstrated a significant inverse association between omega-3 fatty acids consumption and the risk of recurrent VTE (RR=0.45, 95% CI: 0.25 to 0.81; P=0.008). Conclusion: Although current evidence is still insufficient to demonstrate any relationship between fish consumption and the risk of VTE, omega-3 fatty acids consumption seems to be associated with a lower risk of both VTE and recurrent VTE. Further large well-designed prospective cohort studies are warranted to elaborate the issues examined in this study.